Studies of Stress Degradation of Ramosetron Hydrochloride, a 5-HT3 Antagonist - Hossain, Md Mokaram; Jalil, Reza Ul; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Three issues of fundamental importance in drug therapy are safety, efficacy and stability. Extensive information derived from stress degradation studies of Ramosetron HCl will expand the scientific thought further to ensure to achieve the intended quality of Ramosetron HCl as drug substance and drug products available in the market. Stress degradation screening of Ramosetron HCl was conducted in aqueous, 0.1N, 0.5N, 1.0N and 2.0N acid-base and oxidative (3, 5 and 10 % H2O2) conditions and photo degradation. No degradation was found in aqueous condition at 60°C for 7 days. Acceptable degradations were found in 0.5 N, 1N and 2N HCl at 70ºC for 7 days, 0.1N NaOH at 60°C for 2 days, 3% hydrogen peroxide at room temperature for 1, 2 and 3 hours in dark and 3.6 million lux fluorescence light or 600 watts hour/m2 UV light. Among other applied stress conditions, the base hydrolysis and oxidative methods degraded Ramosetron hydrochloride more drastically than the other stressed conditions. Dhaka Univ. J. Pharm. Sci. 17(1): 9-17, 2018 (June)